Distillation of Essential Oils from Pontianak Orange Peel Wastes and Its Utilization for Aromatherapy Soap - Hidayati, Hidayati (Biopropal Industri, 2012)
Orange (Citrus nobilis var. microcarpa) is the main commodities in Pontianak. Production of essential oils from orange peel wastes and its use for soap aromatherapy substance could improve its economic value. This study is aimed to produce the essential oils from orange peel wastes with the highest limonene content by distillation. Its application for aromatherapy soap substance also evaluated. Distillation of essential oils from orange peels was performed at 1000C and 1100C for 4, 5, 6 and 7 hours. The results showed that at 1000C for 7 hours produced the highest limonene content, reach 97.69%. The essential oils color was pale yellow, specific gravity 0.84, refractive index 1.47, solubility in 90% ethanol 1:1 (transparent), acid value 0.143% and ester number 5.37. The aromatherapy soap produced with addition of 3.6% of limonene oils is in accordance with SNI 06-3532-1994 except for water content parameter.